Chemical Composition of Covered and Naked Spring Barley Varieties and Their Potential for Food Production - Šterna Vita; Zute Sanita; Jansone Inga; Kantane Inara (Polish Journal of Food and Nutrition Sciences)
By developing new varieties suitable for the production of healthy products, given the greater consumer and manufacturer focus on the functional ingredients and nutritional properties of barley, new opportunities to incorporate barley into human foods are created. Therefore, the aim of investigation was to analyze grain composition of barley varieties and perspective breeding lines bred in Latvia and to evaluate its functional ingredients depending on varieties, year and nitrogen fertilizer rates. The content of protein, starch, β-glucans, total dietary fiber, composition of amino acids and α-tocopherol were determined in the studied samples. The results of two-year analysis showed that the protein content in barley grain samples ranged from 10.5 to 13.9%, total dietary fiber – from 18.74 to 20.82%, but the content of β-glucans ranged from 3.44 to 4.97%. The content of α-tocopherol was determined to range from 7.21 to 8.58 mg/kg, and the sum of essential amino acids – from 31.5 to 38.9 g/kg. Although covered barley varieties demonstrated a higher content of such functional ingredients as α-tocopherol, total dietary fiber and β-glucans, naked barley grains had a higher protein content, the sum of essential amino acids, and, particularly lysine, was not far behind the content recommended by nutrition experts.